Solvency and wholesale funding cost interactions at UK banks - Dent, Kieran; Hacıoğlu Hoke, Sinem; Panagiotopoulos, Apostolos (Journal of Financial Stability, 2021)
We study the interaction between solvency and funding costs at UK banks. We use the market-based leverage ratio as a proxy for market participants’ perceptions of bank solvency. We investigate the impact that changes in this ratio have on banks’ CDS premia, which are a proxy for their marginal cost of wholesale funding. We find that a negative shock to market participants’ perception of banks’ solvency is associated with an increase in banks’ marginal cost of wholesale funding. We find evidence that this negative relationship is nonlinear, i.e. the responsiveness of funding costs to a shock to solvency is greater at lower initial levels of solvency.